Memory of visual paired associates in healthy aging. A transcultural study - Álvarez González, Miguel Ángel; Cruz, Teresa; Balmaseda Serrano, Raquel; Gracia Morilla, Candela; García Morales, Leidy; Fernández-Cahill, María; Manzanero, Antonio L. (Consejo General de la Psicologia de Espana, 2022)
The present study contrasts performance in an immediate and delayed recall test across two aging populations without known neurological disorders from different cultural contexts. A total of 191 individuals, 97 Cubans and 94 Spaniards, participated. The age range was between 60 and 90 years (M= 70.6; SD= 6.8). The participants were evaluated with an immediate and a 30-minute delayed visual paired associates (VPA) test. Results showed no significant differences in the correct answers of the immediate and delayed recall depending on the nationality and gender of the participants. Age and educational level affected performance in immediate and delayed memory. A lower age and a higher level of education produced a better performance. In conclusion, the VPA test can be useful to assess memory across populations of different cultural contexts. Age negatively affected performance in immediate and delayed memory tasks in healthy aging. Educational level could be a protective factor, associated with the formation of the cognitive reserve. © 2021 Sociedad Universitaria de Investigación en Psicología y Salud. Publicado por Consejo General de Colegios Oficiales de Psicólogos, España. Este es un artículo Open Access bajo la CC BY-NC-ND licencia (http://creativecommons.org/licencias/by-nc-nd/4.0/).
Keywords: cognitive decline; cognitive reserve; contexto cultural; cultural context; declinar cognitivo; envejecimiento sano; episodic memory; healthy aging; memoria episódica; pares visuales asociados; reserva; visual paired associates; Scopus; Emerging